2017
DOI: 10.1007/s13238-017-0372-z
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based assessment of disease-related mutations in human voltage-gated sodium channels

Abstract: Voltage-gated sodium (Nav) channels are essential for the rapid upstroke of action potentials and the propagation of electrical signals in nerves and muscles. Defects of Nav channels are associated with a variety of channelopathies. More than 1000 disease-related mutations have been identified in Nav channels, with Nav1.1 and Nav1.5 each harboring more than 400 mutations. Nav channels represent major targets for a wide array of neurotoxins and drugs. Atomic structures of Nav channels are required to understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
135
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(139 citation statements)
references
References 72 publications
3
135
0
1
Order By: Relevance
“…To further validate our approach and demonstrate its suitability for other target sequences, we applied the same strategy to the intracellular linker connecting DI and II of NaV1.5. Similar to the DIII-IV linker, mutations or aberrant PTMs in this region of NaV1.5 have been implicated in cardiac disease 23,29 . Using appropriate N and C constructs, together with both recombinantly expressed and synthetic versions of a peptide XNav1.5 variant corresponding to amino acids 505 to 527 of NaV1.5, we demonstrated that tPTS can be used to probe the function of different intracellular regions of NaV1.5 in Xenopus oocytes.…”
Section: Replacing Nav15 Inter-domain Linkers With Synthetic Peptidesmentioning
confidence: 99%
“…To further validate our approach and demonstrate its suitability for other target sequences, we applied the same strategy to the intracellular linker connecting DI and II of NaV1.5. Similar to the DIII-IV linker, mutations or aberrant PTMs in this region of NaV1.5 have been implicated in cardiac disease 23,29 . Using appropriate N and C constructs, together with both recombinantly expressed and synthetic versions of a peptide XNav1.5 variant corresponding to amino acids 505 to 527 of NaV1.5, we demonstrated that tPTS can be used to probe the function of different intracellular regions of NaV1.5 in Xenopus oocytes.…”
Section: Replacing Nav15 Inter-domain Linkers With Synthetic Peptidesmentioning
confidence: 99%
“…The inheritance pattern is autosomal dominant and highly penetrant, except for the very rare syndrome of congenital myopathy which is autosomal recessive. Over 70 mutations of SCN4A have been identified in patients with skeletal muscle disorders (Huang et al, 2017; Lehmann-Horn and Jurkat-Rott, 1999). Genotype-phenotype associations have emerged (Miller et al, 2004; Rüdel et al, 1993), wherein specific mutations are consistently found to cause a particular clinical syndrome amongst the 6 allelic disorders of the muscle sodium channelopathies (Fig.…”
Section: Xx3 Overview Of Nav14 Mutationsmentioning
confidence: 99%
“…Na V channelopathies lead to serious diseases affecting nervous system function, heart rhythm, and skeletal muscle contraction (see review in (Huang et al 2017)). Pathologies of isoforms expressed in the CNS include Na V 1.1 defects that are associated with Dravet syndrome, severe epilepsy, sleep disturbance, and cognitive impairment.…”
Section: Biological Contextmentioning
confidence: 99%